Posted by **Anonymous** on Monday, August 25, 2008 at 6:25pm.

Solve log4 x + log4(x-2)=log4(15)

I know how do the example in my book but I don't know what I'm doing wrong here.

log4 x + log4(x-2)=log4(15)

log4 [x + log4(x-2)]=log4(15)

(x^2 + x)=4

x^2 + x-4=0

- Logarithms -
**Reiny**, Monday, August 25, 2008 at 6:43pm
I see two major errors

1. from log A + log B = log (A x B)

your second line should have been

log4 [x(x-2)]=log4(15)

then in your third line

the right side should have been 15, not 4

so

x(x-2) = 15

x^2 - 2x - 15 = 0

(x-5)(x+2) = 0

x = 5 or x = -2, but x+-2 does not work since you cannot take the log of a negative

so x=5

## Answer This Question

## Related Questions

- Algebra 2 - Simplify: 1. 2log10^5+log10^4 2. 2log3^6-log3^4 3. log4^40-log4^5 4...
- Algebra II - Solve, round to four decimal places if necessary: log4(x-9)=2 ...
- Precalc - Using logarithms to rewrite the expression: 1.) log4.(4)^3x= 2.) 6 ...
- precalc - I don't understand how to do these w/o calc. I tried to write it in a ...
- Math(Please check) - solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I ...
- Math - solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I do?
- math - Solve the equation algebraically. Round the result to three decimal ...
- Logarithm help - Write each expression as a single logarithm I need help really...
- Math - Evaluate the expression without using a calculator: log4(2)= ____? Use a ...
- math - log4(2x+4)-3 =log4 3

More Related Questions